Algae: The green solution for basic sanitation - Gomes, Keyla Nunes Farias; Pereira, Julianne Soares; Jardim, Geovana Espíndola; Santiago, Patrícia Soares; Rocha, Leandro; Faria, Robson Xavier (Seven Editora, 2024)
The use of algae in basic sanitation and water purification is a promising approach. Algae, both microalgae and macroalgae, are photosynthetic organisms that play a crucial role in removing nutrients and contaminants from effluents. They have been extensively studied and applied in water and wastewater treatment systems due to their effective and sustainable ability to absorb nutrients such as nitrogen, phosphorus, and organic pollutants. Compared to conventional methods, algae-based technologies offer significant environmental benefits, including lower energy consumption and reduced reliance on chemicals. Successful examples worldwide, such as in Qingdao (China) and San Francisco (USA), demonstrate successful implementation cases, resulting in improved water quality, the promotion of sustainability, and the protection of aquatic ecosystems. In the future, it is essential to continue investing in research and development to optimize these technologies and promote their global implementation, aiming to address global challenges related to freshwater scarcity and water pollution. DOI:https://doi.org/10.56238/sevened2024.018-006